Exploration of Maqasid Al-Shariah Concepts in The Development of Islamic Economic Policies - Karimullah, Suud Sarim (Institut Agama Islam Negeri Metro, 2023)
This study examines the concept of maqasid al-shariah in the context of Islamic economic policy development, emphasizing its understanding, implementation in policy, and evaluation of its impact on society and welfare. The research employs a literature review method, conducting a comprehensive analysis of relevant sources across various disciplines. The findings indicate that maqasid al-shariah serves as a moral compass within Islamic economics, providing a foundation for a just, sustainable, and ethical economy. Its implementation requires the establishment of robust Islamic financial institutions, the regulation of economic activities in accordance with Islamic law, and the preservation of moral values in business practices. The evaluation of its impact underscores the significant role of Islamic economics in safeguarding the core objectives of protecting religion, property, life, intellect, and lineage. This study highlights the ongoing relevance of maqasid al-shariah as a guiding framework for Islamic economic policies, offering a bridge between theoretical principles and practical applications to foster a more just and ethical society.